2006
DOI: 10.1128/mcb.01412-05
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Insulin Secretion and β-Cell Mass by Activating Signal Cointegrator 2

Abstract: Activating signal cointegrator 2 (ASC-2) is a transcriptional coactivator of many nuclear receptors (NRs) and other transcription factors and contains two NR-interacting LXXLL motifs (NR boxes).In the pancreas, ASC-2 is expressed only in the endocrine cells of the islets of Langerhans, but not in the exocrine cells. Thus, we examined the potential role of ASC-2 in insulin secretion from pancreatic ␤-cells. Overexpressed ASC-2 increased glucose-elicited insulin secretion, whereas insulin secretion was decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 67 publications
3
25
0
Order By: Relevance
“…Activating signal cointegrator-2 (Asc2), a transcriptional coactivator of nuclear receptors has also been shown to be involved in glucose sensitive insulin secretion and the maintenance of β cell mass (Yeom et al 2006). The mechanisms are unclear, although there is evidence that the liver X receptor (LXR), which is also involved in glucose sensing in β cells (Efanov et al 2004), and the MODY1 gene Hnf4α might be involved.…”
Section: Maintenance Of β Cell Functionmentioning
confidence: 99%
“…Activating signal cointegrator-2 (Asc2), a transcriptional coactivator of nuclear receptors has also been shown to be involved in glucose sensitive insulin secretion and the maintenance of β cell mass (Yeom et al 2006). The mechanisms are unclear, although there is evidence that the liver X receptor (LXR), which is also involved in glucose sensing in β cells (Efanov et al 2004), and the MODY1 gene Hnf4α might be involved.…”
Section: Maintenance Of β Cell Functionmentioning
confidence: 99%
“…Disruption of both NCoA6 alleles in mice results in embryonic lethality due to defective development of the placenta, heart, and liver (3,18,23,51). Disruption of one NCoA6 allele in mice accelerates polyomavirus middle-T-antigen-induced mammary tumorigenesis, reduces insulin secretion, and slightly affects postnatal growth (23,43,47). In addition, specific deletion of the NCoA6 gene in mouse mammary epithelial cells decreases mammary ductal growth regulated by estrogen and partially impairs milk synthesis (33).…”
mentioning
confidence: 99%
“…In a previous study we found that ASC-2 + / − mice greater than 20week-old had a higher plasma glucose level than wild-type mice of the same age [27]. However, we recently recognized that plasma glucose levels were not significantly different in young (10-weekold) ASC-2 + / − and wild-type mice (Supplementary Figure S1 at http://www.BiochemJ.org/bj/447/bj4470437add.htm).…”
Section: Increased Insulin Sensitivity Of Young Asc-2 + / − Micementioning
confidence: 95%
“…Islet isolation was accomplished by collagenase digestion and differential centrifugation through Ficoll gradients using a previously described procedure [27]. After isolation, islets were incubated overnight in RPMI 1640 medium (11 mM glucose) and supplemented with 100 IU/ml penicillin, 100 μg/ml streptomycin and 10 % (v/v) FBS (fetal bovine serum).…”
Section: Islet Isolation and Glucose-stimulated Insulin Secretionmentioning
confidence: 99%
See 1 more Smart Citation